Finite Representation of Classes of Isomorphic Groupoids - Nazarov, Maxim N. (Journal of Siberian Federal University. Mathematics & Physics, 2015)
We consider an alternative representation of finite groupoids in the form of hypergraphs with three-vertex edges. Automorphism classes of vertices and edges of this hypergraphs are linearly ordered by a natural indexing algorithm based on a maxi-code for three-dimensional adjacency matrix of the hypergraph. With respect of this indexing is constructed a finite set description for the classes of isomorphic groupoids.